Quantitative ethnobotany of Calotropis procera and associated vegetation: a step forward for conservation and management practice in northern areas of Pakistan - Siraj; Nasrullah Khan (Ethnobotany Research and Applications, 2021)
Background: Calotropis procera is one of the most effective herbal medicinal shrubs. Although many studies have explored the ecological aspects of Calotropis procera; still a lack of documented information about the quantitative ethnobotanical and conservation attributes on this medicinally endangered plant and its associated vegetation in the Northern regions of Pakistan. Methods: Semi-structured questionnaires, group discussions, and field observations were used to collect data on the therapeutic uses of C. procera, its availability, difficulties, and future conservation measures. These data were quantitatively analyzed using Person’s carrying traditional knowledge (PCTK), Relative Frequency Citation (RFC), the report used for plant part (RUPP), plant part value (PPV), specific use (SU), Use Value (UV) and Jaccard Index (JI). Results: Forty-five plant species belonging to 31 families and 34 genera were recorded in the northern areas of Pakistan. The Asteraceae was a species-rich family (8 species), followed by Poaceae and Euphorbiaceae (4 species each). Quantitative analysis revealed that the most used plant parts (PPV) and use values (UV) for medicinal purposes were leaves and latex (1.462 and 1.295). Furthermore, C. procera had a higher PCTK score for thorn pricking (96 %) and wound healing (93.5 %). The UV varied from 0.08 (Lamium amplexicaule L.) to 0.79 (C. procera W.T. Aiton). The RFC ranged from 0.06 (Xanthium strumarium L) to 0.28 (C. procera W.T. Aiton). Concerning the similarities between the present work and neighboring countries, India shows higher similarities (5.52) that may reflect the common flora and similar cultural norms. Keywords: Calotropis procera, Conservation, Northern areas, Quantitative ethnobotany